Electrochemical behaviour of 5-(Furan-2-yl)-4-(p-tolyl)-2,4-dihydro-1,2,4-triazole-3-thione by using glassy carbon electrode - Dilgin, Yusuf; Cansiz, Ahmet; Cetin, Ahmet; Kutulay, Pelin; Oral, Ayhan; Yilmaz, Selahattin (Asian Journal of Chemistry, 2007)
The electrochemical study of a thiotriazole compound, 5-(furan-2-yl)-4-(p-tolyl)-2,4-dihydro-1,2,4-triazole-3-thione (TTA) was performed by cyclic voltammetry (CV) and differential pulse voltammetry (DPV) using glassy carbon electrode (GCE) as working electrode and an Ag/AgCl reference electrode. The dependence of the current on pH and scan rate was investigated in the Britton Robinson Buffer. The best results for electrooxidation of TTA were obtained in basic media (pH 11.0 containing 5 % DMSO). This compound display one irreversible oxidation peak, which is attributed to a dimerization process involving the formation disulphide derivative.
Keywords: thiotriazole; electrochemical behaviour; glassy carbon electrode; voltammetry